2013
DOI: 10.1186/1757-2215-6-87
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological spectrum of ovarian sex cord-stromal tumors; 20 years’ retrospective study in a developing country

Abstract: BackgroundOvarian sex cord stromal tumors are rare neoplasms as compared to epithelial tumors. No large study has been done in Pakistan to find out the frequencies of various sex cord stromal tumors and their clinicopathological behavior in our region. The purpose of our study was to determine the various histological patterns and clinical features of ovarian sex cord stromal tumors along with follow-up in our set-up.MethodsIt is a retrospective observational study. The study was conducted in section of Histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 25 publications
3
36
2
5
Order By: Relevance
“…This is in accordance with the available international literature. [6][7][8][9] The histomorphological observations in our study are similar to other reports. 6,7 We observed that most of the tumors were unilateral, ranging from 5 to 15 cm in size.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This is in accordance with the available international literature. [6][7][8][9] The histomorphological observations in our study are similar to other reports. 6,7 We observed that most of the tumors were unilateral, ranging from 5 to 15 cm in size.…”
Section: Resultssupporting
confidence: 91%
“…This is slightly lower as compared to other studies. 6,7 The most common clinical presentation in our study was abdominal pain and lump, whereas the signs and symptoms of hormonal excess such as virilization and precocious puberty and menstrual irregularities were relatively less. This is in accordance with the available international literature.…”
Section: Resultsmentioning
confidence: 68%
“…In mucinous cystadenocarcinoma (0.5%), the atypical cells were also seen invading the ovarian stroma. Ovarian sex cord-stromal tumors are uncommon neoplasms that represent approximately 7% of 25 all ovarian tumors. Only single case of fibroma as well as a single case of fibroma-thecoma was found in our study.…”
Section: Singh M Et Almentioning
confidence: 99%
“…Son dönemlerde bunlara CD99, CD56 ve "Steroidenic factor (SF-1)", FOXL2 gibi immünohistokimyasal boyalar da ilave edilmektedir. 4,13 Seks kord stromal tümörle-rinin alt tipleri arasında immünohistokimyasal ekspresyon profilleri de örtüşmektedir.…”
Section: Discussionunclassified